Liquid crystalline nanoconfined growth of PANI on rGO for enhanced electrochemical glucose sensing - Tawade, Anita K.; Kumar, Praveen; Tayade, Shivaji N.; Sharma, Geetarani K.; Luwang, Meitram Niraj; Sharma, Kiran Kumar K. (Nanoscale, 2026)
We report here a new strategy for the successful synthesis of a hybrid 2D nanocomposite via the in situ functionalization of graphene oxide (GO) with aniline monomers in a bi-solvent swollen liquid crystalline lamellar mesophase (SLCLM) nanoreactor. The synthesized nanocomposite product revealed possible simultaneous reactions at the edge and basal plane of GO. A mechanism for the transformation via simultaneous nucleophilic attack and spontaneous polymerization, forming a reduced graphene oxide-polyaniline (rGO-PANI) nanocomposite, is proposed. The multistep plausible reaction mechanism for the functionalization of the GO edge -COOH group is achieved by successful synthesis, followed by isolation and characterization of the N-phenyl anthranilic acid derivative as an intermediate product. Furthermore, the detection of CO2 evolution as a by-product during the reaction complements the plausible mechanism for the incorporation of (-C Xi C-) graphyne-type edges and formation of new -C-N- and O-H bonds in the rGO-PANI nanocomposite. These results are supported by FT-IR, Raman, XPS, SAXS, and C-13 NMR spectroscopy analyses. A reduced graphene oxide-polyaniline (rGO-PANI) modified glassy carbon electrode was developed for glucose sensing, exhibiting a wide linear range (0.554-10 & micro;M), low detection limit (50 pM), and high sensitivity (372 660 & micro;A mM(-1) cm(-2)). The sensor demonstrated excellent selectivity against common interferents (ascorbic acid, uric acid, and dopamine), reproducibility (RSD < 5%), and stability over 10 000 s with minimal signal loss. The detection of glucose from human metabolites, such as urine and sweat, achieved 98-100% recoveries for spiked glucose, confirming its practical applicability. These results establish rGO-PANI as a robust platform for sensitive and selective glucose detection.